Penggunaan Bebat Perineum Untuk Mempercepat Penyembuhan Luka Perineum Pada Ibu Nifas - Triwik Sri Mulati; Dewi Susilowati (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstract Background: Childbirth is the outcome of a process of conception (the baby) to live from the uterus to the outside world. In the process of spending the baby frequent injury in the birth canal or perineal wound (Mochtar, 2012). The purpose of this study to prove the effect of perineal bandage to cure the perineal wound. Method: The research design was quasi experiment with untreated control group design. Samples in this researh were some post partum mother who suffered wounds perineum in BPM Klaten some 118 people. Bivariate data analysis using statistical test used was t – tes. Result: Results from this study is that there was no influence the bandage perineum (kempitan) to cure maternal perineal wound. Perineum will cause pain and discomfort to the mother postpartum, with pain and swelling in the perineum makes the mother fear for early mobilization, to overcome this, the mother post partum have bandaging perineum (kempitan) to reduce pain and swelling, so the mother post partum can do early mobilization. Conclusion: If the mother can do early mobilization so that the maternal perineal wound may be able cured as soon as possible. Bandaging perineum (kempitan) is a bandage on the perineum given after using sanitary apkins and panty to reduce pain and swelling.